2020
DOI: 10.1097/j.pain.0000000000001903
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cerebrospinal fluid neuroinflammatory mediators depending on osteoarthritis pain phenotype

Abstract: Neuroinflammation is implicated in the development and maintenance of persistent pain states, but there are limited data linking cerebrospinal fluid (CSF) inflammatory mediators with neurophysiological pain processes in humans. In a prospective observational study, CSF inflammatory mediators were compared between patients with osteoarthritis (OA) who were undergoing total hip arthroplasty due to disabling pain symptoms (n = 52) and pain-free comparison controls (n = 30). In OA patients only, detailed clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 90 publications
2
18
0
Order By: Relevance
“…The current research was part of a prospective, observational study (neuroPSI, neuro pain sleep immunology) of patients with disabling OA‐related pain undergoing THA (Bjurström et al., 2020). The study was conducted at a fast‐track, orthopedic surgical center (Hässleholm Hospital).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current research was part of a prospective, observational study (neuroPSI, neuro pain sleep immunology) of patients with disabling OA‐related pain undergoing THA (Bjurström et al., 2020). The study was conducted at a fast‐track, orthopedic surgical center (Hässleholm Hospital).…”
Section: Methodsmentioning
confidence: 99%
“…The following QST measures were defined as preoperative objective pain outcomes: pressure pain detection threshold (PPDT), pressure pain tolerance threshold (PPTT), and conditioned pain modulation (CPM). We have previously described our QST protocol in detail (Bjurström et al, 2020).…”
Section: Predictor: Preoperative Sleep Qualitymentioning
confidence: 99%
“…Peng et al found in aged rats that parecoxib inhibits hepatectomy-induced IL-1β and TNF-α expression in the hippocampus through the downregulation of the COX-2/PGE2 pathway [ 23 ]. Bjurstrom et al [ 16 ] reported that the proinflammatory mediators in cerebrospinal fluid are associated with persistent post-surgical pain. In clinical trials, due to technical limitations, real-time monitoring of central neuroinflammation is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The observational data unpublished from patients after liver surgery revealed a CPSP prevalence of 48.6%. Previous studies [ 16 , 17 ] were used to determine the sample size. Based on an α of 5% and a power of 80%, a sample size of 44 patients per group was sufficient to detect a difference between the parecoxib and placebo groups, given the occurrence rate of 20 and 50%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Peng et al found in aged rats that parecoxib inhibits hepatectomy-induced IL-1β and TNF-αexpression in the hippocampus through downregulation of the COX-2/PGE2 pathway [10]. Bjurstrom et al reported that proin ammatory mediators in cerebrospinal uid are associated with persistent postsurgical pain [18]. In clinical trials, due to technical limitations, real-time monitoring of central neuroin ammation is challenging to achieve.…”
Section: Discussionmentioning
confidence: 99%